Plasma-treated Langmuir–Blodgett reduced graphene oxide thin film for applications in biophotovoltaics - Ibrahim, Siti Aisyah; Jaafar, Muhammad Musoddiq; Ng, Fong Lee; Phang, Siew Moi; Kumar, G. Ghana; Abd Majid, Wan Haliza; Periasamy, Vengadesh (Springer, 2018)
The surface optimization and structural characteristics of Langmuir–Blodgett (LB) reduced graphene oxide thin (rGO) film treated by argon plasma treatment were studied. In this work, six times deposition of rGO was deposited on a clean glass substrate using the LB method. Plasma technique involving a variation of plasma power, i.e., 20, 60, 100 and 140 W was exposed to the LB-rGO thin films under argon ambience. The plasma treatment generally improves the wettability or hydrophilicity of the film surface compared to without treatment. Maximum wettability was observed at a plasma power of 20 W, while also increasing the adhesion of the rGO film with the glass substrate. The multilayer films fabricated were characterized by means of spectroscopic, structural and electrical studies. The treatment of rGO with argon plasma was found to have improved its biocompatibility, and thus its performance as an electrode for biophotovoltaic devices has been shown to be enhanced considerably.